Adam Chmielowski: patriota, artysta, zakonnik, święty - Skrzydlewska, Beata (Biografistyka Pedagogiczna, 2021)
Most studies on the life and work of Adam Chmielowski have not been of a scholarly nature and have primarily focused on his philanthropic activities. The most attention has been drawn to the years when he adopted the religious habit of the Third Order of St Francis (at that time he took the monastic name of Albert) as well as to the time when he founded the Albertine Brothers Congregation and later the Congregation of the Albertine Sisters. In fact, the activity started by Brother Albert is extremely significant; his involvement in helping the wretched, alcoholics and homeless allowed these people to believe in the dignity that belongs to every person. In books and articles that have been written about Chmielowski, it has not been clearly stated that there were many paths that led the future saint to the decision to help people who today would be described as the excluded. When undertaking a biographical analysis, it should be emphasised that Adam Chmielowski was a complex character, who spent quite a long time searching for his life’s path. It must be admitted, however, that every field of his activity led ultimately to the work of helping others, a great work of which he was the creator. It seems that too little attention has been paid to his artistic work, which was an extremely important part of his life. For a long time, it seemed to his friends, to his family and even to himself that this was the path he would follow throughout his life. This path, like that of creating a work of art, required his full commitment.